2022
DOI: 10.1038/s41415-022-4137-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a quality improvement initiative to reduce denture loss in an acute hospital

Abstract: Background Denture loss is a significant problem for patients admitted to hospital in the UK. Initiatives aimed at staff and patients have been introduced at many hospitals to try and reduce and solve this issue. Aim This investigation aimed to evaluate the impact of a quality improvement programme on denture loss at an acute hospital, including the reasons dentures were reported as lost or broken and who reported them. Method Information on dentures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…77 A recurring problem is the loss of a prosthesis during a hospital stay or loss/misplacement associated with cognitive decline, which can be debilitating. 78 Notwithstanding the limitations of 3D printed dentures, an important benefit of additive manufacturing in complete/partial denture prosthodontics is the relative ease with which replacement prostheses can be inexpensively fabricated when a patient loses a denture. By developing prostheses in 3D on compatible software, it is possible to make minor alterations to prosthetic designs and provide functional, wax-free printed trial prostheses before finalizing the design.…”
Section: Applications In Removable Prosthodonticsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 A recurring problem is the loss of a prosthesis during a hospital stay or loss/misplacement associated with cognitive decline, which can be debilitating. 78 Notwithstanding the limitations of 3D printed dentures, an important benefit of additive manufacturing in complete/partial denture prosthodontics is the relative ease with which replacement prostheses can be inexpensively fabricated when a patient loses a denture. By developing prostheses in 3D on compatible software, it is possible to make minor alterations to prosthetic designs and provide functional, wax-free printed trial prostheses before finalizing the design.…”
Section: Applications In Removable Prosthodonticsmentioning
confidence: 99%
“…While traditional denture fabrication continues to serve as the gold standard, 3D printed dentures are slowly coming into the mainstream, and this trend is expected to continue as baby boomers age 77 . A recurring problem is the loss of a prosthesis during a hospital stay or loss/misplacement associated with cognitive decline, which can be debilitating 78 . Notwithstanding the limitations of 3D printed dentures, an important benefit of additive manufacturing in complete/partial denture prosthodontics is the relative ease with which replacement prostheses can be inexpensively fabricated when a patient loses a denture.…”
Section: Innovations For the Prevention Of Oral Diseasementioning
confidence: 99%
“…One of the troublesome problems with denture handling in care facilities and wards are the loss of dentures [2]. This represents a sporadic problem.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Michaeli et al reported 30 cases of denture loss in 8 months at facilities for older adults and inpatient wards, although the number of subjects was unknown [4]. Further, Doshi et al state that denture loss is still a major problem these days [2].…”
Section: Introductionmentioning
confidence: 99%